Microstructure and mechanical properties of cast in-situ TiAl matrix composites reinforced with (Ti, Nb)2AlC particles. (5th November 2017) - Lapin, J.; Klimová, A.; Gabalcová, Z.; Pelachová, T.; Bajana, O.; Štamborská, M.
Abstract: The in-situ TiAl matrix composites with nominal compositions of Ti-44.5Al-8Nb-0.8Mo-0.1B- x C (at.%), where x is ranging from 1.4 to 4.8 at.%, were prepared by casting. The microstructure of the as-cast composites consists of primary (Ti, Nb)2 AlC particles distributed in the matrix composed of lamellar γ(TiAl) + α2 (Ti3 Al) and γ phase regions with a small amount of β/B2 phase. The chemical composition of some coarse carbides is not homogeneous and central regions enriched by C are identified to be (Ti, Nb)C phase. The mean aspect ratio of the primary carbide particles decreases and their volume fraction and shape factor increase with increasing content of C. A linear relationship is identified between the volume fraction of the carbide particles and average content of C in the composites. The heat treatments lead to the formation of fine secondary carbide particles within the matrix. The mean grain size of the as-cast composites increases during the heat treatments. The Vickers hardness, compression yield strength, Charpy impact value and dynamic fracture toughness of the heat-treated composites decrease with the increasing volume fraction of carbide particles. The brittle fracture behaviour of the in-situ composites includes crack deflection, delamination on the matrix-carbide interfaces and pull-out of the carbide particles from the γ matrix. Graphical abstract: Highlights: The in-situ TiAl matrix composites reinforced with (Ti, Nb)2 AlC particles have been prepared by casting. The increasing content of C at a fixed content of Al, Nb, Mo and B promotes formation of the γ matrix. The volume fraction of carbide particles increases linearly with increasing content of C. The room-temperature mechanical properties decrease with increasing volume fraction of carbide particles. The primary carbide particles act as effective obstacles to crack propagation.